Effects of plyometric training on components of physical fitness in prepuberal male soccer athletes: The role of surface instability - Negra, Y.; Chaabene, H.; Sammoud, S.; Bouguezzi, R.; Mkaouer, B.; Hachana, Y.; Granacher, U. (The Journal of Strength and Conditioning Research, 2017)
Previous studies contrasted the effects of plyometric training (PT) conducted on stable vs. unstable surfaces on components of physical fitness in child and adolescent soccer players. Depending on the training modality (stable vs. unstable), specific performance improvements were found for jump (stable PT) and balance performances (unstable PT). In an attempt to combine the effects of both training modalities, this study examined the effects of PT on stable surfaces compared with combined PT on stable and unstable surfaces on components of physical fitness in prepuberal male soccer athletes. Thirty-three boys were randomly assigned to either a PT on stable surfaces (PTS; n = 17; age = 12.1 ± 0.5 years; height = 151.6 ± 5.7 cm; body mass = 39.2 ± 6.5 kg; and maturity offset = -2.3 ± 0.5 years) or a combined PT on stable and unstable surfaces (PTC; n = 16; age = 12.2 ± 0.6 years; height = 154.6 ± 8.1 cm; body mass = 38.7 ± 5.0 kg; and maturity offset = -2.2 ± 0.6 years). Both intervention groups conducted 4 soccer-specific training sessions per week combined with either 2 PTS or PTC sessions. Before and after 8 weeks of training, proxies of muscle power (e.g., countermovement jump [CMJ], standing long jump [SLJ]), muscle strength (e.g., reactive strength index [RSI]), speed (e.g., 20-m sprint test), agility (e.g., modified Illinois change of direction test [MICODT]), static balance (e.g., stable stork balance test [SSBT]), and dynamic balance (unstable stork balance test [USBT]) were tested. An analysis of covariance model was used to test between-group differences (PTS vs. PTC) at posttest using baseline outcomes as covariates. No significant between-group differences at posttest were observed for CMJ (p > 0.05, d = 0.41), SLJ (p > 0.05, d = 0.36), RSI (p > 0.05, d = 0.57), 20-m sprint test (p > 0.05, d = 0.06), MICODT (p > 0.05, d = 0.23), and SSBT (p > 0.05, d = 0.20). However, statistically significant between-group differences at posttest were noted for the USBT (p < 0.01, d = 1.49) in favor of the PTC group. For most physical fitness tests (except RSI), significant pre-to-post improvements were observed for both groups (p < 0.01, d = 0.55-3.96). Eight weeks of PTS or PTC resulted in similar performance improvements in components of physical fitness except for dynamic balance. From a performance-enhancing perspective, PTC is recommended for pediatric strength and conditioning coaches because it produced comparable training effects as PTS on proxies of muscle power, muscle strength, speed, agility, static balance, and additional effects on dynamic balance.